Financial knowledge of pre-university students: age and gender - Ruiz-Palomo, Daniel; Galache-Laza, María Teresa; Cisneros-Ruiz, Ana José; García-Lopera, Francisca (My University, 2022)
Financial education is essential to improve the well-being of society at large by avoiding, to a large extent, erroneous financial decisions. It is, therefore, necessary to inculcate adequate financial literacy from an early age. The aim of this paper is to identify the possible effects of age and gender on the acquisition of financial literacy, exploring the potential interrelationships between them. Applying a set of multilevel (mixed effects) regression models to a sample of 9,917 pre-university students from 175 training centres in Andalusia, our results show that age and gender are significantly related to the pre-university student’s financial literacy. Moreover, gender plays a moderating role in the relationship between age and financial literacy acquisition. The results of this study have practical implications for teachers, students, school principals and educational planners because they help to understand better the critical factors in financial literacy at the pre-university level.
Keywords: Finanzas - Educación; Financial literacy; Financial knowledge; Age; Gender; Pre-university students